Encyclopedia of Life Sciences 2020
DOI: 10.1002/9780470015902.a0029089
|View full text |Cite
|
Sign up to set email alerts
|

Body Size Evolution in Crocodylians and Their Extinct Relatives

Abstract: Crocodylians are currently facing evolutionary decline. This is evinced by the rich fossil record of their extinct relatives, crocodylomorphs, which show not only significantly higher levels of biodiversity in the past but also remarkable morphological disparity and higher ecological diversity. In terms of body size, crocodylians are mostly large animals (>2 m), especially when compared to other extant reptiles. In contrast, extinct crocodylomorphs exhibited a 10‐fold range in body sizes, with early terrest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
2
1
Order By: Relevance
“…This niche partitioning is shown by the co-occurrences of multiple tethysuchians associated with diverse diets. Finally, unlike other studies (Godoy et al 2019;Godoy and Turner 2020;Lakin et al 2020), we found a positive correlation between body length (using the log-transformed SL as proxy) and temperature. These results may be explained by the difference in a preferential season of growth duration.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This niche partitioning is shown by the co-occurrences of multiple tethysuchians associated with diverse diets. Finally, unlike other studies (Godoy et al 2019;Godoy and Turner 2020;Lakin et al 2020), we found a positive correlation between body length (using the log-transformed SL as proxy) and temperature. These results may be explained by the difference in a preferential season of growth duration.…”
Section: Discussioncontrasting
confidence: 99%
“…However, these analyses excluded PNC and used ordinary least squares and GLS instead of phylogenetic comparative methods. A significant relationship has been found for the crocodilian crown-group using the same methodology (Godoy et al 2019; Godoy and Turner 2020), suggesting that larger body sizes are associated with cooler climates. Similar results were found when only extant crocodylomorphs were analyzed (Lakin et al 2020).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation